Preparation method and products of ultrathin titanium oxide nanosheets rich in oxygen and titanium vacancies

By peeling, drying, annealing and hydrogen reduction treatment of the titanium oxide nanosheets, ultra-thin titanium oxide nanosheets rich in oxygen vacancy and titanium vacancy were successfully prepared, which solved the problem of low light capture efficiency of existing TiO2 materials and achieved the Highly efficient photocatalytic properties.

CN118579831BActive Publication Date: 2025-02-14ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410797095.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-02-14
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The existing TiO2 materials have limitations in light capture efficiency, and it is very difficult to introduce oxygen vacancy and titanium vacancy in TiO2, affecting its photoelectric performance.

Method used

Ultrathin titanium oxide nanosheets rich in oxygen vacancy and titanium vacancy were prepared by peeling, drying, annealing and hydrogen reduction treatment.

Benefits of technology

The prepared product is anatase-type titanium oxide ultra-thin nanosheets, with a complete and uniform surface, excellent photocatalytic activity, and can show strong light absorption in both the visible and ultraviolet light bands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118579831B_ABST
    Figure CN118579831B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing ultrathin titanium oxide nanosheets rich in oxygen and titanium vacancies, comprising: (1) using titanium oxide nanosheets as raw materials, obtaining a single-layer titanium oxide nanosheet suspension after exfoliation; (2) after drying the single-layer titanium oxide nanosheet suspension, annealing it in air, cooling it to room temperature, and then placing it in a reactor heated to 500-750°C, and introducing a mixed gas composed of hydrogen and carrier gas into the reactor, keeping it at this temperature for a period of time, and then rapidly cooling it to room temperature to obtain ultrathin titanium oxide nanosheets rich in oxygen and titanium vacancies. The preparation method disclosed in this invention is simple and controllable; the product obtained is anatase-type ultrathin titanium oxide nanosheets with a complete and uniform surface, no particulate matter, a thickness of no more than 2 nm, but a large lateral size; the product is also rich in both oxygen and titanium vacancies, and the vacancy content can be effectively controlled, which is expected to be used as a high-efficiency catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method of an ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies and a product thereof. Background Art

[0002] Titanium dioxide (TiO2) is a metal oxide material that has been widely studied in recent decades, especially in the fields of energy and environmental applications. However, its wide band gap (~3.2e V) allows it to capture only about 5% of solar energy, which greatly hinders its light capture efficiency. Many studies have been devoted to narrowing the band gap of TiO2 by doping with impurity atoms, thereby improving the light absorption of TiO2 in the visible light region (accounting for 43% of solar energy). However, such band structure engineering may cause problems such as carrier capture, poor crystal thermal stability, and secondary contamination of dopants.

[0003] Defects in materials often exhibit unusual effects, which may lead to significant advances in various scientific fields. Well-managed defects (e.g., impurities, structural vacancies, etc.) in the location and concentration of materials can lead to more ideal properties. TiO2 is generally considered to be an oxygen-deficient compound, and its n-type semiconductor properties mainly come from oxygen vacancies and interstitial titanium. Oxygen vacancies generally come from escaped oxygen. Defects in TiO2 also include titanium vacancies, which are mainly obtained in oxygen-rich environments, and they form acceptor-type centers responsible for the p-type properties. The np junction is considered to be a very promising structure that can promote charge separation and thus improve the optoelectronic properties of semiconductors. Therefore, the homojunction of oxygen vacancies and titanium vacancies may provide Ti O2 with unidirectional conductivity from n-type to p-type, thereby enhancing the electronic conductivity and charge transport properties of Ti O2. However, from the perspective of stoichiometry, it is very difficult to introduce oxygen vacancies and titanium vacancies in TiO2 at the same time, and it is rarely mentioned in current research.

[0004] Two-dimensional nanomaterials are a class of ultra-thin sheet-like crystals with atomic or molecular-level thickness, and their lateral dimensions are generally larger than the micrometer scale. This two-dimensional characteristic leads to some unique physical, chemical and mechanical properties that cannot be achieved by other traditional bulk materials. The atomic-level thickness is generally smaller than the mean free path of transport of most particles, including electrons, excitons and phonons, which forces them to follow ballistic transport rather than scattering or diffusion. At the same time, the ultra-thin nature of the material gives it excellent optical transparency and rapid response to external stimuli, exposing a large number of active sites, which is crucial for the study of catalysis, optoelectronics and sensors.

[0005] Since layered materials are connected by weak van der Waals forces between layers and by strong covalent and ionic bonds within the layers, the preparation of two-dimensional materials is currently focused on the exfoliation, vapor deposition, and self-assembly of layered materials. However, since anatase titanium oxide is an intrinsic non-layered material, it continues the crystallographic structure of the bulk phase, has surface unsaturated bonds and high surface activity, and there is no weak van der Waals force between layers within the crystal, and all its atoms are connected by strong chemical bonds, making the preparation of its ultra-thin two-dimensional structure still a great challenge at present. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention discloses a method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies. The method is simple and controllable. The prepared product is anatase-type titanium oxide ultrathin nanosheet with a complete and uniform surface, no granular matter, a thickness not exceeding 2nm, but a large lateral size. The product is also rich in oxygen vacancies and titanium vacancies, and the vacancy content can be effectively regulated, so it is expected to be used as a high-efficiency catalyst.

[0007] The specific technical solutions are as follows:

[0008] A method for preparing an ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies comprises the following steps:

[0009] (1) using titanium oxide nanosheets as raw materials and obtaining a single-layer titanium oxide nanosheet suspension after peeling;

[0010] (2) After the monolayer titanium oxide nanosheet suspension is dried, it is first placed in air for annealing treatment, cooled to room temperature, and then placed in a reactor heated to 500-750° C., and a mixed gas consisting of hydrogen and a carrier gas is introduced into the reactor. After being kept warm for a period of time, it is suddenly cooled to room temperature to obtain the ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies;

[0011] The annealing treatment is performed at a temperature of 350-550°C.

[0012] The preparation method disclosed in the present invention uses titanium oxide nanosheets as raw materials, and sequentially undergoes peeling, drying, annealing and hydrogen reduction treatment to obtain anatase-type titanium oxide ultra-thin nanosheets rich in oxygen vacancies and titanium vacancies. Through detailed characterization, it is found that after annealing, lepidocrocite-type titanium oxide will be transformed into anatase-type, and titanium vacancies will be introduced at the same time; after further hydrogen reduction treatment, oxygen vacancies will be introduced again, and at a suitable hydrogen reduction treatment temperature, the crystal phase will not be transformed. Therefore, the annealing temperature, the heat treatment system of the hydrogen reduction treatment and the treatment temperature in the present invention play a key role in preparing the target product.

[0013] Experiments have found that if the annealing temperature is too low (such as 300°C), impurity elements will be introduced into the product, significantly reducing the catalytic performance of the product and affecting subsequent applications in photocatalysis and other fields; if the annealing temperature is too high (such as 600°C), the vacancies in the product disappear, which will still significantly reduce the catalytic performance of the product.

[0014] The experiment found that if the heat treatment system of hydrogen reduction treatment is changed to increase and decrease the temperature with the reactor, obvious damage and holes will be observed in the product. If the temperature of hydrogen reduction treatment is too low, no reaction will occur; and if the temperature of hydrogen reduction treatment is too high, the product will no longer be anatase titanium oxide, but a new phase will be produced.

[0015] In step (1):

[0016] The titanium oxide nanosheets are prepared by using rutile titanium dioxide as a raw material and calcining at high temperature, specifically:

[0017] TiO2, Li2CO3, K2CO3 and MoO3 are used as raw materials, and then they are ground evenly and calcined at high temperature. The crude product is washed, dried and then placed in a hydrochloric acid solution to obtain the product.

[0018] The high temperature calcination has a temperature of 800-1200°C.

[0019] In step (1):

[0020] The stripping specifically includes:

[0021] Placing the titanium oxide nanosheet in an intercalation agent solution, and obtaining a single-layer titanium oxide nanosheet suspension after standing or ultrasonic treatment;

[0022] The intercalant solution is selected from tetrabutylammonium hydroxide aqueous solution and / or tetramethylammonium hydroxide aqueous solution;

[0023] The concentration of the intercalant solution is (0.003-0.012) M;

[0024] The molar ratio of titanium oxide nanosheets to intercalation agent is 0.5 to 1.5.

[0025] In step (2):

[0026] The drying is selected from freeze drying, specifically, first pre-cooling with liquid nitrogen, and then placing in a freeze dryer at -50 to -70°C for drying.

[0027] The annealing treatment can be carried out in an air atmosphere, and the annealing treatment time is 1 to 8 hours.

[0028] Preferably, the annealing temperature is 400-500°C.

[0029] In step (2):

[0030] In the mixed gas, the flow rate of hydrogen is 50 to 200 sccm;

[0031] The carrier gas is selected from one or more of argon, nitrogen and neon;

[0032] The volume ratio of hydrogen to carrier gas is 1:(1-3).

[0033] Preferably, in the mixed gas, the flow rate of hydrogen is 150-180 sccm, and the volume ratio of hydrogen to carrier gas is 1:(1-1.5).

[0034] The insulation time is 1 to 4 hours.

[0035] Preferably, the intermediate product after annealing is placed in a reactor heated to 650-750°C.

[0036] It has been found through experiments that the vacancy content in the product can be regulated by controlling the temperature of the hydrogen reduction treatment. When the preferred temperature is 650-750°C, the vacancy content in the prepared product is higher.

[0037] The invention also discloses an ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared according to the above method.

[0038] Characterization shows that the surface of the product prepared by the present invention is complete and uniform, without the presence of granular matter, with a lateral size of 5 to 150 μm and a thickness of no more than 2 nm; the product is anatase-type, rich in oxygen vacancies and titanium vacancies, and the total vacancy content is adjustable, and strong light absorption occurs in both the visible light band and the ultraviolet light band, indicating that it has excellent photocatalytic activity and is expected to be applied in the field of photocatalysis.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The invention discloses a method for preparing an ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies. The titanium oxide nanosheet is used as a raw material, and peeling, drying, annealing and hydrogen reduction treatment are performed in sequence. The raw materials and equipment are simple and the method is highly controllable.

[0041] The product prepared by the present invention is anatase-type titanium oxide ultra-thin nanosheet, which has a complete and uniform surface, no granular matter, a thickness not exceeding 2nm, but a large lateral size of 5 to 150μm; the product is also rich in oxygen vacancies and titanium vacancies, and the vacancy content can be effectively regulated, strong light absorption occurs in both the visible light band and the ultraviolet light band, and has excellent photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1This is an atomic force microscope (AFM) photograph of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared in Example 1;

[0043] Figure 2 Transmission electron microscope (TEM, a) photograph and transmission high resolution image (HRTEM, b) of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared in Example 1;

[0044] Figure 3 The scanning electron microscope (SEM, a) photograph of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in Example 1 and the optical microscope (OM, b) photograph of the ultrathin titanium oxide nanosheets dispersed and spin-coated on a silicon wafer;

[0045] Figure 4 The Raman spectrum of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared in Example 1 is shown, and the Raman spectrum before reduction is given for comparison;

[0046] Figure 5 The X-ray photoelectron spectrum (XPS) of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in Example 1 is shown, and the XPS graph before reduction is given for comparison;

[0047] Figure 6 The electron paramagnetic resonance (EPR) images of the products prepared in Examples 1 to 3 and Comparative Examples 5 and 7 are shown, and the EPR images before reduction are shown for comparison;

[0048] Figure 7 The X-ray diffraction (XRD) spectra of the products prepared in Examples 1 to 3 and Comparative Examples 5 and 7 are shown, and the XRD patterns before reduction are given for comparison;

[0049] Figure 8 The ultraviolet visible absorption spectrum (UV-vis) of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared in Example 1 is shown, and the UV spectrum before reduction is given for comparison;

[0050] Fig. 9 This is the SEM image of the product prepared in Example 2;

[0051] Fig.10 This is the SEM image of the product prepared in Example 3;

[0052] Fig.11 This is the energy dispersive spectrometer (EDS) surface scan element distribution diagram of the product prepared in Comparative Example 1;

[0053] Fig.12 This is the EPR spectrum of the product prepared in Comparative Example 2;

[0054] Fig.13 This is the SEM image of the product prepared in Comparative Example 3;

[0055] Fig.14 This is the SEM image of the product prepared in Comparative Example 5. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto.

[0057] Example 1

[0058] S1: TiO2 (rutile), Li2CO3, K2CO3 and MoO3 were weighed in a molar ratio of 1.73:0.13:1.67:1.27, ground evenly, put into a platinum crucible, and calcined at 1473K for 10h. The product was then washed with water several times and dried to obtain K 0.8 [Ti 1.73 Li 0.27 ]O4. Then K 0.8 [Ti 1.73 Li 0.27 ]O4 was placed in a 1M HCl aqueous solution and stirred for 5 days, with a new HCl aqueous solution replaced every day to prepare H 1.07 Ti 1.73 O4.H2O. 0.005molH 1.07 Ti 1.73 O4.H2O was placed in a 0.005M, 1L tetrabutylammonium hydroxide (TBAOH) aqueous solution and allowed to stand for half a month before peeling to obtain a single-layer titanium oxide nanosheet suspension.

[0059] S2: The prepared single-layer titanium oxide nanosheet suspension is first pre-frozen with liquid nitrogen, then freeze-dried in a freeze dryer, and then placed in a tubular furnace, heated to 400°C in an air environment and maintained for 4 hours for annealing, and then cooled to room temperature. The annealing treatment can remove the tetrabutylammonium hydroxide (TBAOH) inside the titanium oxide nanosheets and promote the recrystallization of the freeze-dried lepidocrocite titanium oxide into anatase titanium oxide rich in titanium vacancies.

[0060] S3: Heat the tubular furnace. When the temperature at the center of the tubular furnace reaches 700°C, use a push-pull rod to push the sample into the center of the furnace tube, and introduce a mixture of 150 sccm hydrogen and 150 sccm argon. After keeping warm for 120 minutes, turn off the hydrogen and keep introducing argon. Pull the sample out of the center area (away from the center of the tubular furnace, equivalent to a sudden drop to room temperature). At this time, argon is used as a protective gas to prevent the sample rich in oxygen vacancies and titanium vacancies from being oxidized. After the temperature drops to room temperature, it can be taken out of the furnace tube. The product is an ultrathin titanium oxide nanosheet aerogel rich in oxygen vacancies and titanium vacancies.

[0061] Figure 1This is an atomic force microscope (AFM) photograph of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared in this example. From the AFM thickness curve, it can be seen that the surface of the ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared is smooth and the thickness is about 1.5 nm.

[0062] Figure 2 Transmission electron microscope (TEM) photos of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment, and transmission high resolution image (HRTEM), (a) is the TEM photo, and (b) is the HRTEM image; from observing Figure (a), it can be found that the surface of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment is smooth, without the presence of granular substances, and no obvious damage; from observing Figure (b), it can be found that spots with weak diffraction intensity appear at the marked position, indicating the presence of titanium vacancies.

[0063] Figure 3 Scanning electron microscope (SEM, a) and light microscope photograph (OM, b) of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment. From observation of Figure (a), it can be found that the interior of the aerogel sample is ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies of continuous size; after the sample prepared in Example 1 is dispersed in the solution and spin-coated on a silicon wafer, it can be found from observation of Figure (b) that the lateral size of the nanosheets can reach 150μm.

[0064] Figure 4 This is the Raman spectrum of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this example. From the figure, it can be found that after the sample is reduced, the main Raman peak undergoes a blue shift and is accompanied by a broadening of the peak, indicating that with the formation of oxygen vacancies, the original symmetry of the sample is destroyed and the disorder increases.

[0065] Figure 5 This is the X-ray photoelectron spectrum (XPS) of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment. By observing the figure, it can be found that the fine spectra of O1s and Ti2p both move toward the direction of low binding energy. This is because as oxygen in titanium oxide escapes to form oxygen vacancies, the electronegativity of the sample decreases.

[0066] Figure 6 This is an electron paramagnetic resonance (EPR) diagram of a series of products including the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment. By observing the EPR of the intermediate product (initial) before reduction, it can be found that after air annealing, its peak is at g=1.998, indicating that there are titanium vacancies at this time. Compared with the initial sample, it is found that after hydrogen reduction treatment, the oxygen vacancies gradually increase, and the EPR peak moves toward the direction of the oxygen vacancies.

[0067] Figure 7The XRD spectra of a series of products including the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment are shown, and the XRD of the intermediate product (initial) before reduction is given for comparison. The comparison shows that after hydrogen reduction treatment, the rutile titanium oxide is still maintained, but the peak position of the XRD spectrum is broadened, indicating that with the increase of oxygen vacancies, the periodic symmetry of the sample decreases.

[0068] Figure 8 This is the ultraviolet-visible absorption spectrum (UV-vis) of the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment. It was observed that the sample before hydrogen reduction had almost no absorption in the visible light band (400-800nm). After reduction, not only did it show strong light absorption in the visible light band, but the absorption intensity in the ultraviolet light (200-400nm) band was also enhanced to a certain extent, indicating that the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this embodiment have the characteristics of strong light absorption and are expected to be used as an efficient photocatalyst.

[0069] Furthermore, the ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies prepared in this example were tested for photocatalytic performance. The same mass (12 mg) of ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies and commercial catalytic nano titanium oxide (P25) were taken to degrade the same mass concentration (1.2×10 -5 ) Rhodamine B solution (RH-B), and observing its concentration degradation curve, it can be found that P25 needs 100 minutes to completely degrade RH-B dye, while this example only needs 5 minutes to completely degrade it. By calculating its rate curve, it can be found that the rate of the sample obtained in this example is 0.465, which is more than 20 times that of P25. This may be because the sample of this example has both titanium vacancies and oxygen vacancies, which can provide more active sites for catalytic reactions, and because oxygen vacancies are positively charged and titanium vacancies are negatively charged, the two vacancies form a large number of built-in electric fields inside the material, which promote the movement of electrons and further accelerate the reaction rate.

[0070] Example 2

[0071] The preparation process is substantially the same as that of Example 1, except that in step S3, the center temperature of the tube furnace is replaced with 600°C.

[0072] observe Figure 6The EPR test results of the product prepared in this embodiment show that the peak position is between titanium vacancies (g=1.998) and oxygen vacancies (g=2.003), which means that this sample has both titanium vacancies and oxygen vacancies. Further comparison between the initial sample and the sample prepared in Example 1 shows that the number of oxygen vacancies and titanium vacancies in the product prepared in this embodiment is increased compared with the initial sample, but slightly less than that of the product in Example 1. Analysis shows that the reason may be due to the lowering of the reduction temperature.

[0073] observe Figure 7 From the XRD spectrum, the physical phase of the product prepared in this example is still anatase titanium oxide.

[0074] Fig. 9 This is a SEM photograph of the product prepared in this example. From the image, it can be found that the complete nanosheet structure is retained without any damage.

[0075] Example 3

[0076] The preparation process is substantially the same as that of Example 1, except that in step S3, the center temperature of the tube furnace is replaced with 500°C.

[0077] observe Figure 6 The EPR test results of the product prepared in this example show that the peak position is between the titanium vacancy (g=1.998) and the sample prepared in Example 1, which indicates that the sample has both titanium vacancies and oxygen vacancies. Further comparison of the initial sample with the samples prepared in Examples 1 and 2 shows that the number of oxygen vacancies and titanium vacancies in the product prepared in this example is slightly higher than that in the initial sample, but both are less than those in Examples 1 and 2. The reason may be due to the lower reduction temperature.

[0078] observe Figure 7 From the XRD spectrum, the physical phase of the product prepared in this example is still anatase titanium oxide.

[0079] Fig.10 This is a SEM photograph of the product prepared in this example. From the image, it can be found that the complete nanosheet structure is retained without any damage.

[0080] Embodiment 4-5

[0081] The preparation process is substantially the same as that of Example 1, with the only difference being that in step S3, the center temperature of the tube furnace is replaced with 650° C. and 750° C. in sequence.

[0082] After characterization, it was found that the prepared ultra-thin titanium oxide nanosheets were rich in oxygen vacancies and titanium vacancies. The EPR test results, XRD test results, thickness and lateral dimensions were comparable to those of Example 1.

[0083] Embodiment 6-7

[0084] The preparation process is basically the same as that of Example 1, with the only difference being that in step S3, the flow rate of the introduced argon gas is replaced with 170 sccm and 180 sccm respectively.

[0085] After characterization, it was found that the prepared ultra-thin titanium oxide nanosheets were rich in oxygen vacancies and titanium vacancies. The EPR test results, XRD test results, thickness and lateral dimensions were comparable to those of Example 1.

[0086] Comparative Example 1

[0087] The preparation process is basically the same as that of Example 1, except that in step S2, the annealing temperature is replaced with 300° C. and kept at this temperature for 4 hours.

[0088] The photocatalytic performance test was carried out in the same manner as in Example 1. The same mass (12 mg) of the comparative sample and the commercial catalytic nano-titanium oxide (P25) were taken to degrade the same mass concentration (1.2×10 -5 ) Rhodamine B solution (RH-B), observing its concentration degradation curve, it can be found that P25 needs 100min to completely degrade RH-B dye, while in this comparative example, 40% RH-B solution is still not degraded after 100min.

[0089] observe Fig.11 From the EDS surface scan spectrum of the product prepared in the comparative example, it can be found that carbon element exists inside the sample.

[0090] Comparative Example 2

[0091] The preparation process is basically the same as that of Example 1, except that in step S2, the annealing temperature is replaced with 600° C. and kept at this temperature for 4 hours.

[0092] Fig.12 From the EPR spectrum of the product prepared in this comparative example, it can be seen that the vacancies in the sample disappear and no obvious peaks appear, which may be caused by the annealing temperature being too high.

[0093] Comparative Example 3

[0094] The preparation process is basically the same as that in Example 1, except that in step S3:

[0095] The annealed sample was first placed in the center of the tube furnace and heated from room temperature to 700°C at a heating rate of 25°C / min. When the temperature in the center of the tube furnace reached the target temperature, a mixed gas consisting of 150sccm hydrogen and 150sccm argon was introduced. After keeping warm for 120 minutes, the introduction of hydrogen was stopped, and the introduction of 150sccm argon was still maintained. The sample was cooled at a cooling rate of 25°C / min along with the furnace, and the sample was taken out after it dropped to room temperature.

[0096] Fig.13 This is the SEM photo of the sample prepared in this comparative example. From the observation of the picture, it can be found that the sample is still in the shape of nanosheets, but there are many damages on the surface of the nanosheets, and the holes in some areas are relatively large, which can reach 100nm.

[0097] Comparative Example 4

[0098] The preparation process is substantially the same as that of Example 1, except that in step S3, the center temperature of the tube furnace is replaced with 400°C.

[0099] The test found that the reduction reaction did not occur at this reaction temperature.

[0100] Comparative Example 5

[0101] The preparation process is substantially the same as that of Example 1, except that in step S3, the center temperature of the tube furnace is replaced with 800°C.

[0102] observe Figure 6 The EPR test results of the product prepared in the comparative example show that after hydrogen reduction treatment at this temperature, the original titanium vacancies and oxygen vacancies disappear.

[0103] observe Figure 7 From the XRD spectrum, it can be seen that with the increase of temperature, the original rutile structure of the product prepared in this comparative example collapsed and a new phase was generated.

[0104] Fig.14 This is a SEM photograph of the product prepared in this comparative example. By observing the figure, it can be found that the morphology of the nanosheets is severely damaged, the thickness of the nanosheets is increased, and sintering occurs.

[0105] Comparative Example 6

[0106] The preparation process is substantially the same as that of Example 1, except that in step S3, the center temperature of the tube furnace is replaced with 900°C.

[0107] observe Figure 6 The EPR test results of the product prepared in the comparative example show that after hydrogen reduction treatment at this temperature, the original titanium vacancies and oxygen vacancies also disappear.

[0108] observe Figure 7 From the XRD spectrum, it can be seen that with the increase of temperature, the original rutile structure of the product prepared in this comparative example collapsed and a new phase was generated.

[0109] SEM characterization showed that at this reaction temperature, the prepared oxidized nanosheets were severely damaged and the nanosheets became thicker.

[0110] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not used to limit the present invention. A technician in the technical field to which the present invention belongs can also make several simple deductions, deformations, substitutions or combinations based on the concept of the present invention. These deductions, deformations, substitutions or combinations also fall within the scope of the claims of the present invention.

Claims

1. A method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies, characterized in that: The steps include: (1) Using titanium oxide nanosheets as raw materials, a single-layer titanium oxide nanosheet suspension is obtained after peeling; (2) After the monolayer titanium oxide nanosheet suspension is dried, it is first placed in air for annealing treatment, cooled to room temperature, and then placed in a reactor heated to 500-750° C., and a mixture of hydrogen and carrier gas is introduced into the reactor. After being kept warm for 1-4 hours, the suspension is suddenly cooled to room temperature to obtain the ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies; The annealing treatment is performed at a temperature of 350-550° C. and a time of 1-8 h.

2. The method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies according to claim 1, characterized in that: In step (1): The titanium oxide nanosheets are prepared by using rutile titanium dioxide as a raw material and calcining at high temperature; The high temperature calcination has a temperature of 800-1200°C.

3. The method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies according to claim 1, characterized in that: In step (1): The stripping specifically includes: Placing the titanium oxide nanosheet in an intercalation agent solution, and obtaining a single-layer titanium oxide nanosheet suspension after standing or ultrasonic treatment; The intercalant solution is selected from tetrabutylammonium hydroxide aqueous solution and / or tetramethylammonium hydroxide aqueous solution; The concentration of the intercalant solution is (0.003~0.012)M; The molar ratio of titanium oxide nanosheets to intercalation agent is 0.5-1.

5.

4. The method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies according to claim 1, characterized in that: In step (2): In the mixed gas, the flow rate of hydrogen is 50-200 sccm; The carrier gas is selected from one or more of argon, nitrogen and neon; The volume ratio of hydrogen to carrier gas is 1:(1~3).

5. The method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies according to any one of claims 1 to 4, characterized in that: In step (2), the annealing treatment is performed at a temperature of 400-500°C.

6. The method for preparing ultrathin titanium oxide nanosheets rich in oxygen vacancies and titanium vacancies according to claim 5, characterized in that: In step (2): The annealed intermediate product is placed in a reactor heated to 650-750°C; In the mixed gas, the flow rate of hydrogen is 150-180 sccm, and the volume ratio of hydrogen to carrier gas is 1:(1-1.5).

7. An ultrathin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies prepared according to the method according to any one of claims 1 to 6, characterized in that: The ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies is anatase-type.

8. The ultra-thin titanium oxide nanosheet rich in oxygen vacancies and titanium vacancies according to claim 7, characterized in that: The lateral size is 5~150 μm and the thickness is no more than 2 nm.

Citation Information

Patent Citations

  • Ultra-thin mixed crystal titanium dioxide nanometer sheet and preparation method and application thereof

    CN106915769A

  • Spatially separated double-vacancy titanium dioxide homojunction catalyst as well as preparation method and application thereof

    CN114984937A